Effect of converting enzyme inhibition with captopril on baroreflex sensitivity (Revista Española de Fisiología, 1988)
Clinical and experimental data suggest that both Captopril and angiotensin II (AII) reduce baroreflex responsiveness, and the main action of this converting enzyme inhibitor (CEI) seems clear to suppress AII synthesis.The aim of this work is to investigate this striking similarity of effects.We have verified that CEI (4 mg/kg) originates tachycardia significantly lower (P less than 0.001) than that produced in response to a similar hypotension elicited by an unspecific vasodilator: sodium nitroprusside (10-45 micrograms/kg min).CEI SQ 20881 has been reported to increase plasma vasopressin concentrations (AVP); this peptide is also known to modify baroreflex responses and has a small direct negative chronotropic effect.However, our determinations of AVP do not show any difference between the control group and the group treated with Captopril (4.78 +/- 0.87 and 5.26 +/- 0.19 pg/ml respectively).On the other hand, although CEI did not modify the rapid responses of heart rate (HR) to changes of mean arterial pressure (MAP), the decrease of MAP induced by nitroprusside was higher in the group treated with Captopril than in control group; it could mean a baroreflex ability decrease to buffer the hypotension.However, AII elicited a strong impairment of both rapid responses of HR and the buffering of hypotension produced by NP, these actions being suggested as centrally mediated.These results could indicate that the suppression of peripheral AII synthesis and therefore, the lack of pre- and postjunctional sympathetic potentiation owing to this hormone, is responsible for the absence of tachycardia under Captopril treatment.